Girls of South Coast Today: A Study of Policy of Child-Marriage in Gunung Kidul Yogyakarta - Any Sundari (Jurnal Perempuan, 2016)
Our girls today faced with a condition that is very susceptible to the risk of child marriage age. The expectation that the child marriage be stopped immediately hit by a thick wall of patriarchal culture intertwined with the social structure, economic and political. Conditions of poverty, difficult geographical location, access to education are minimals, and the lack of willingness of policy makers have worsened the child’s age. But amid all the complexity of the state of marriage age of the child, there is a good practice the elimination of child marriage as in Gunung Kidul, Yogyakarta. Marriage age is quite high in some areas, such as in sub district in Gedangsari Gunung Kidul has made policy makers together with the residents making network-based integration MoU (the collective agreement) at the district level for the elimination of child marriages. This agreement contains cooperation of various institutions, both on the level of schools, villages, health centers, law enforcement officers, to institute the service of women in the sub-district level to end the marriage age of the child. Attempts to move along this done because all people agreed that the root causes of child marriage is not a single, then the handle should give space to all parties to move together.